The Mediating Role of Entrepreneurial Intention and The Moderating Role of Displacement in Entrepreneurial Behavior Determinants - Desy Ayu Safitri; Agus Wahyudin; Sandy Arief (Universitas Negeri Semarang, 2026)
This study aims to examine entrepreneurial behavior among university students and to investigate the effects of perceived desirability, perceived feasibility, and propensity to act, with entrepreneurial intention as a mediating variable and displacement events as a moderating variable. Entrepreneurial behavior reflects the realization of entrepreneurial intention through concrete actions in creating, developing, and managing business ventures. This research employed a quantitative approach using an ex post facto causal research design. The population consisted of 3.221 students from the Faculty of Economics and Business, Universitas Negeri Semarang, cohorts 2023–2024, with a sample of 356 respondents selected using the Slovin formula and proportionate random sampling. Data were collected through a validated and reliable questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0, including direct, mediation, and moderation analyses. The results indicate that perceived desirability, perceived feasibility, propensity to act, and entrepreneurial intention have significant direct effects on entrepreneurial behavior, while perceived desirability, perceived feasibility, and propensity to act also significantly influence entrepreneurial intention. Entrepreneurial intention mediates the relationships between these antecedent variables and entrepreneurial behavior, and displacement events strengthen the effect of entrepreneurial intention on entrepreneurial behavior. These findings contribute to entrepreneurial behavior literature by emphasizing the role of displacement events in accelerating the transformation of intention into action and highlight the importance of practice-based learning, action-oriented academic environments, and institutional support in fostering student entrepreneurship.